O tecnomorfismo enquanto processo composicional - INGRID MAYUMI YAMAZATO DE SOUZA (2025)
This work aims to understand how the concept of musical technomorphism, that is, the abstraction of technological resources and their application to traditional instrumental means, can be seen as a compositional model and, mainly, to understand how technological tools impact the procedural aspect of musical composition. Thus, we seek to understand how electroacoustic montage can influence the instrumental writing process. The methodological approach adopted for this research consists of performing comparative analyses between acousmatic and instrumental pieces by composers Hans Tutschku, Patricia Alessandrini and Felipe de Almeida Ribeiro, aiming to present the similarities and differences between the creative processes in both contexts. To this end, the theoretical references used are Tatiana Catanzaro's work on the definition of technomorphism, Pierre Schaeffer's theory and typomorphology to support the analyses of electroacoustic pieces, and François Delalande's cognitive musicology to understand and systematize the stages of each composer's creative processes. Furthermore, the construction of the musical instrument through composition is investigated from the perspective of Helmut Lachenmann. Finally, the analyses and research carried out inform the compositional practice of the researcher herself, who presents her account of the creation process of the piece “Mobius Strip” for cello and electronics as a way of demonstrating the practical application of the ideas raised by the research.